How does Digitalisation Transform Business Models in Ropax Ports? A Multi-Site Study of Port Authorities - Chen, Yiran (International Information Management Association, 2025)
This article investigates the relationship between digitalisation and business model changes in RoPax ports. The study is based on six RoPax ports in Northern Europe, examining their digitalisation efforts and the resulting changes in their business models, leading to further digital transformation. The paper offers insights by reviewing relevant literature on digitalisation’s role in business model innovation and its application in ports. The findings reveal that digitalisation supports relevant business model changes concerning port operation integration within logistics chains, communication, documentation flow, and cargo flow optimisation. However, exploring digitalisation’s potential for diversifying value propositions is still limited. Most digitalisation efforts enhance existing operations through automation, monitoring, and decision-making support. The study contributes to understanding port business models and offers practical implications for RoPax ports’ digital transformation.